Measuring The Ethical Awareness and Ethical Orientation of Accountants - Hanung Triatmoko (Jurnal Akuntansi dan Bisnis, 2006)
This research aimed to identify individual ethical dimension in ethical decision making (ethical awareness) and impacts of ethical dimension in ethical decision making (ethical orientation).The respondents of this study involved students of Accounting program who had taken Auditing 1 at the Economic Faculty of Sebelas Maret University. Data were obtained by distributing research ques-tionnaires to students. Data analysis used factor analysis and regression. Among the four dimensions of ethical i.e. moral equity, relativism, contractualism and utilitarian (and egoism), result analysis showed that the highest mean was relativism. This research results were consistent with Cohen’s (1996). Meanwhile regression analysis results indicated that relativism turned out to be the most sig-nificant factor affecting ethical measurement. This result was not consistent with previous research stating that moral equity was the most significant factor.